Pengembangan Media Pembelajaran Interaktif Berbasis Flash Pada Materi Klasifikasi Hewan Vertebrata Mata Pelajaran Biologi Kelas VII SMP - Titin Fitri Ningsih; Hariman Bahtiar; Yupi Kuspandi Putra (Fakultas Teknik Universitas Hamzanwadi, 2022)
The development of technology has entered all areas of life, one of which is in the field of education. As well as the importance of learning media for teachers and students in carrying out the teaching and learning process to make it more interesting, effective and efficient, especially during the COVID-19 pandemic as it is today. So that teachers must regulate teaching and learning activities to continue even though they are through an online system, and ensure learning activities to attract more students' interest, reduce student boredom in learning, and make it easier for students to understand the material quickly. For this reason, interactive learning media is needed to make it easier for teachers and students to carry out the teaching and learning process, especially during the pandemic, besides that teachers also find it helpful in conveying material to students through interactive learning media. By using Adobe Flash software. Computer software used to create animated 2-dimensional (2D) moving images. It will be applied to the study of the classification of vertebrate animals. It is hoped that it will help teachers in biology subjects to visualize the classification of vertebrate animals in 2D objects. Teachers in carrying out their role in the learning process, need tools that can convey information to students. So that it can be used as a means to deliver learning material.Keywords: Learning media, animation, animal classification, adobe flash, covid19.